The activation pattern of macrophages in giant cell (temporal) arteritis and primary angiitis of the central nervous system. Issue 3 (20th December 2013) - Mihm, Bernhard; Bergmann, Markus; Brück, Wolfgang; Probst‐Cousin, Stefan
<x xml:space="preserve">Abstract</x> To determine if the pattern of macrophage activation reflects differences in the pathogenesis and clinical presentation of giant cell arteritis and primary angiitis of the central nervous system, specimens of 10 patients with giant cell arteritis and five with primary angiitis of the central nervous system were immunohistochemically studied and the expression of the macrophage activation markers 27E10, MRP14, MRP8 and 25F9 was determined in the vasculitic infiltrates. Thus, a partly different expression pattern of macrophage activation markers in giant cell arteritis and primary angiitis of the central nervous system was observed. The group comparison revealed that giant cell arteritis cases had significantly higher numbers of acute activated MRP14‐positive macrophages, whereas primary angiitis of the central nervous system is characterized by a tendency toward more MRP8‐positive intermediate/late activated macrophages. Furthermore, in giant cell arteritis comparably fewer CD8‐positive lymphocytes were observed. These observations suggest, that despite their histopathological similarities, giant cell arteritis and primary angiitis of the central nervous system appear to represent either distinct entities within the spectrum of granulomatous vasculitides or different stages of similar disease processes. Their discrete clinical presentation is reflected by different activation patterns of macrophages, which may characterize giant cell arteritis as a more acute process and primary angiitis of the central nervous system as a more advanced inflammatory process.